SYNTHESIS, CHARACTERIZATION AND PERFORMANCE OF COPPER-ZINC OXIDE WITH MIXED PROMOTER CATALYST FOR CO2 HYDROGENATION TO METHANOL - ABD HALIM, NADIA SYAZANA (2019)
Catalytic CO2 hydrogenation to methanol is considered as one of the feasible ways to utilize excess CO2 and mitigates global warming issue. However, the catalytic route is still having an issue on amount of CO2 converted and the methanol selectivity